2017
DOI: 10.4314/ejhs.v27i2.10
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional status of under five children in Ethiopia: a systematic review and meta-analysis

Abstract: BACKGROUND: Undernutrition is the outcome of insufficient food intake and recurrent infectious diseases. The baseline levels of undernutrition remain so high that Ethiopia still needs to continue substantial investment in nutrition.Therefore, the aim of this study was to obtain estimates of over-time trends in the prevalence of undernutrition in Ethiopia and to determine risk factors for undernutrition among children of under five years of age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
116
4
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(149 citation statements)
references
References 32 publications
21
116
4
8
Order By: Relevance
“…Effect size was pooled from all eligible studies using the DerSimonian-Laird Random effects model (REM) for the meta-analysis 11 . This model is preferred because it is based on the assumption that a distribution of effects exists, resulting in heterogeneity among study results 12 . The results were presented in a table as forest plots; additionally prevalence rates, ORs, and 95% CIs were obtained for each study inserted into the model and for the overall estimate.…”
Section: Resultsmentioning
confidence: 99%
“…Effect size was pooled from all eligible studies using the DerSimonian-Laird Random effects model (REM) for the meta-analysis 11 . This model is preferred because it is based on the assumption that a distribution of effects exists, resulting in heterogeneity among study results 12 . The results were presented in a table as forest plots; additionally prevalence rates, ORs, and 95% CIs were obtained for each study inserted into the model and for the overall estimate.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, one article was found by hand searching of the reference lists of the included studies. Thus, a total of 9 studies [4,[22][23][24][25][26][27][28][29] were included in the current umbrella review. The study selection and screening process is shown in Fig.…”
Section: Literature Search Findingsmentioning
confidence: 99%
“…The specific malnutrition conditions assessed by the SRM studies were stunting, wasting, and underweight. Two meta-analyses were done on the prevalence and the determinants of stunting, underweight, and wasting [4,25]. The specific IYCF practice indicators assessed were exclusive breastfeeding, early initiation of breastfeeding, timely initiation of complementary feeding, dietary diversity, meal frequency, and minimum acceptable diet.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations